Comparison between application of platelet rich plasma and mucosal advancement flap in patients with high transsphincteric anal fistulas: a randomized control trial. Issue 5 (28th March 2022) - Hermann, Jacek; Cwaliński, Jarosław; Banasiewicz, Tomasz; Kołodziejczak, Barbara
Abstract: Background: There is still a search for a standard method of therapy for high anal fistulas. The aim of this trial was a comparison between a modified two stage minimally invasive procedure, consisting of loose‐seton placement with the subsequent application of platelet rich plasma with mucosal advancement flap for the treatment of high transsphincteric anal fistulas of crypto‐glandular origin. Methods: The study was designed as a prospective, randomized trial including 96 patients. Curettage of fistulous tracts, and loose‐seton placement was performed in those patients with active inflammation, and if the diameter of a fistulous tract exceeded 3 mm. Afterwards, the patients were randomly assigned to either the PRP group or MAF group, consisting of 49 patients, and 47 patients, respectively. Results: There was no significant statistical difference ( p = 0.152) between both investigated groups of patients regarding closure of fistulas since it was achieved in 35 (71.43%) patients from group I, compared to 27 (57.45%) patients from group II. The diameter of fistulous tracts below 4 mm exerted a significant impact ( p < 0.001) on the healing process after PRP application because fistulas with the narrow tracts were closed in 34 (87.18%) patients, whereas a wider fistula was healed in 1 (10%) patient. Conclusion: The local application of PRP in high, unbranched, and with narrow tracts trans‐sphincteric anal fistulas of crypto‐glandular origin, following loose‐seton drainage is an effective, simple, and a safe method of therapy with a low rate of morbidity. Abstract : There is still a search for a standard method of therapy for anal fistulas due to a high rate of recurrences after previously used methods. The study shows, that the local application of PRP in high anal fistulas with narrow tracts, following loose‐seton drainage is an effective, simple, and safe method of therapy with a low rate of morbidity.